Staying lean for life - Graff, Cynthia Stamper (Torrance, CA Griffin Publishing Group, 1999)
An innovative 8-week program of winning strategies for lifetime weight maintenance
D., unk., 01/2006
Keywords: Weight Maintenance; Diet; Weight Loss; Health; Fitness -- Nutrition